Analysing spatial data gained from walking interviews and psychogeographic group tours - Aled Singleton (GISRUK 2021, 2021)
This paper asks whether there is potential to complement existing Geographic Information Systems (GIS) practice by taking different routes through the Census and other data which relates to places. For example, my PhD research researched ageing, the lifecourse and emotional attachments to place by deploying a methodology which includes interviews inspired by walks and psychogeographic group walking tours. One output from this project is a collective narrative structured along a six-stage walk of 5.8 km. Mapped as a GPX line, could such threads be used to link with other data and therefore provide new ways of understanding the characteristics of places?